Electrochemical production of free available chlorine - Isa, M.H.; Kutty, S.R.M.; Yusoff, H.A.M.; Bashir, M.J.K.; Farooqi, I.H. (2009)
Common water/wastewater disinfection methods use chlorine or its compounds. These are, however, associated with transportation and storage hazards. From a safety point of view, it would therefore be better to produce the disinfectant on-site to minimise transport and storage risks. This study evaluates the suitability of using titanium-based electrodes for the generation of free available chlorine (FAC) for water/wastewater disinfection. Comparison was made with results obtained with a graphite anode. A series of laboratory experiments were conducted at room temperature (27 ± 1 °C) in a 250 mL electrochemical cell. A statistical (factorial) design of experiments was adopted to evaluate the effect of operating parameters viz., electrolyte (NaCl) concentration, current density and reaction time on (FAC) generation. The results show performance of Ti-based anode to be far better than that of graphite anode. The data fitted well with a quadratic model (R2 = 0.8693). Over 76 mg/L FAC was produced with the Ti-based anode at NaCl concentration 3g/L, current density 6 mA/cm2 and reaction time 60 minutes, compared to only 7.81 mg/L using graphite anode under identical reaction conditions.